Anti-measles immunity assessment in Ukrainian health workers and school teachers - Volyanskiy, A. Y.; Kuchma, I. Y.; Kuchma, M. V.; Klisa, A. A.; Stepnova, Yu. B. (Mechnikov Institute of Microbiology and Immunology, 2019)
Аdults suffer from measles harder than children and more frequently have complications. Medics and school teachers are at increased risk of measles disease. In the case of measles, medics and teachers can infect a large number of people in contact with them with possible serious consequences. The study of anti-measles humoral immunity in doctors and teachers of Ukraine during the measles epidemic in the country is to identify and vaccinate susceptible individuals. Materials and methods In February-March 2019, the levels of specific anti-measles IgG in blood serum of 981 medics and 308 teachers aged 18 to 85 were analyzed. The concentration of anti-measles IgG was determined by ELISA using Ridascreen enzyme-linked immunosorbent assays produced by r-Biopharm (Germany) using the Lisa Scan EM enzyme-linked immunosorbent analyzer (Czech Republic). In accordance with the instructions measles IgG levels of 150 mIU/ml or less were considered a negative result, from 151 to 200 mIU/ml inclusive - a dubious result, above 200 mIU/ml - a positive result. Statistical processing of the obtained data was carried out using non-parametric statistics methods with the Atte Stat 12.0.5 statistical software package integrated into Microsoft Excel 2013. The average values of IgG concentration by age groups are equal to sample medians, since sample distributions do not fit the normal distribution criteria according to Kolmogorov-Smirnov confidence criterion estimates. Results and discussion. It was shown that the largest number of measles-susceptible medics and teachers was observed in the age group of 18 to 27 years (7.5% did not have a protective level of specific anti-measles IgG, and 5.6% showed a dubious level of protection). In the age groups from 28 to 37 years old and from 38 to 47 years old, a rather large number of measles-susceptible individuals were also detected (5.3% and 4.6% with no protective level of anti-measles IgG and 5.0% and 3.7 % - with a dubious level of protection, respectively). The minimum number of medics and teachers unprotected from measles was determined in the group aged 48 to 57 years (0.6% of negative and 0.3% of doubtful results), and among the group over 57 years of age, there were no individuals with a lack of protective levels of antibodies to measles virus. The possible reasons for the predominance of teachers and health workers unprotected from measles in the age groups from 18 to 47 years and the absence of unprotected people over 57 years of age are discussed. Conclusion The authors of the article concludes that there is no need for vaccination against measles in medics and teachers over 57 years of age and recommends vaccination of representatives of other age groups only after determining of the anti-measles immunity level, since more than 90% of the tested population have protective IgG levels.
Keywords: vaccination; measles; specific anti-measles IgG; health workers; school teachers